2019
DOI: 10.1093/eurpub/ckz186.229
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of a screening program for cardiovascular diseases in Kazakhstan

Abstract: Background Cardiovascular diseases (CVD) occupy leading positions in the mortality of the Republic of Kazakhstan (RK). In RK CVD screening is performed with 40-years of age. Objectives: to evaluate the effectiveness of screening over time. Methods We conducted a survey of 121 patients with CVD, identified on screening. Results The average age patients in surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Nevertheless, in some primary healthcare facilities in Kazakhstan, there has been identified the need to strengthen the work (as screening programs on CVD, etc) to provide comprehensive care to patients with CVD. 34 In addition, Kulkaeva et al observed the low awareness of the Kazak population regarding CVD risk factors, 35 which led to intensify the work in this area, including among rural residents. 36 Other factors which influence high levels of mortality can include low adherence of patients with arterial hypertension to treatment, and very low clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in some primary healthcare facilities in Kazakhstan, there has been identified the need to strengthen the work (as screening programs on CVD, etc) to provide comprehensive care to patients with CVD. 34 In addition, Kulkaeva et al observed the low awareness of the Kazak population regarding CVD risk factors, 35 which led to intensify the work in this area, including among rural residents. 36 Other factors which influence high levels of mortality can include low adherence of patients with arterial hypertension to treatment, and very low clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), approximately 1.28 billion adults aged 30–79 years worldwide have hypertension, with the majority (two-thirds) living in low- or middle-income countries [ 9 ]. In Kazakhstan, the prevalence of arterial hypertension in the general population ranges from 15.2% to 27%, and, among women, it is around 40%, as reported by various sources [ 10 ]. Moreover, epidemiological studies conducted by Alikhanova et al reveal that the predominant health issues affecting the adult population are related to circulatory system diseases, characterised by elevated blood pressure [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the WHO, arterial hypertension is one of the most common non-specific diseases, accounting for 30% of all deaths. According to a number of sources, the prevalence of arterial hypertension in general population in Kazakhstan varies from 15.2 to 27% and among women is about 40% [16].…”
Section: Introductionmentioning
confidence: 99%